CDNA-AFLP analysis reveals differential gene expression in incompatible interaction between infected non-heading Chinese cabbage and Hyaloperonospora parasitica. (27th July 2016) - Xiao, Dong; Liu, Shi-Tuo; Wei, Yan-Ping; Zhou, Dao-Yun; Hou, Xi-Lin; Li, Ying; Hu, Chun-Mei
Abstract: Non-heading Chinese cabbage ( Brassica rapa ssp. chinensis ) is one of the main green leafy vegetables in the world, especially in China, with significant economic value. Hyaloperonospora parasitica is a fungal pathogen responsible for causing downy mildew disease in Chinese cabbage, which greatly affects its production. The objective of this study was to identify transcriptionally regulated genes during incompatible interactions between non-heading Chinese cabbage and H. parasitica using complementary DNA-amplified fragment length polymorphism (cDNA-AFLP). We obtained 129 reliable differential transcript-derived fragments (TDFs) in a resistant line 'Suzhou Qing'. Among them, 121 upregulated TDFs displayed an expression peak at 24–48 h post inoculation (h.p.i.). Fifteen genes were further selected for validation of cDNA-AFLP expression patterns using quantitative reverse transcription PCR. Results confirmed the altered expression patterns of 13 genes (86.7%) revealed by the cDNA-AFLP. We identified four TDFs related to fungal resistance among the 15 TDFs. Furthermore, comparative analysis of four TDFs between resistant line 'Suzhou Qing' and susceptible line 'Aijiao Huang' showed that transcript levels of TDF14 ( BcLIK1 _A01) peaked at 48 h.p.i. and 25.1-fold increased in the resistant line compared with the susceptible line. Similarly, transcript levels of the other three genes, TDF42 ( BcCAT3 _A07), TDF75 ( BcAAE3 _A06) and TDF88 ( BcAMT2 _A05) peaked at 24, 48 and 24 h.p.i. with 25.1-, 100- and 15.8-fold increases, respectively. The results suggested that the resistance genes tended to transcribe at higher levels in the resistance line than in the susceptible line, which may provide resistance against pathogen infections. The present study might facilitate elucidating the molecular basis of the infection process and identifying candidate genes for resistance improvement of susceptible cultivars. Abstract : Plant defense: Chinese cabbage foils fungus The genes activated in a mildew-resistant cabbage suggest possible targets for engineering new, resistant varieties. Non-heading Chinese cabbage (also called bok choy or pak choi) is a widely grown green vegetable, susceptible, like most cabbages, to the fungal disease downy mildew. Chemical control of downy mildew is unreliable, and resistant varieties might be a better means of prevention. Chun-Mei Hu and colleagues of Nanjing Agricultural University, China, used a low-cost genetic method to explore the genes expressed in a resistant Chinese cabbage variety, 'Suzhou Qing, ' inoculated with downy mildew. Over 120 genes were strongly activated during fungal infection. The authors suggest that the mildew fungus triggers a complex set of metabolic pathways in 'Suzhou Qing, '; some of the genes involved may prove useful targets for breeding more resistant varieties.